Antibiogram and plasmid profiling from Edwardsiella tarda isolated from freshwater fish in east coast Malaysia - Lee Seong Wei; Najiah Musa; Chuah Tse Seng (Universiti Malaysia Terengganu, 2011)
This study was carried out to investigate the antibiogram, plasmid profiling and Multiple Antibiotic Resistance (MAR) index of Edwardsiella tarda isolated from freshwater-fish cultures. To date, the information on antibiogram of local E. tarda isolates is still lacking. Therefore, this study was conducted to reveal the most suitable choice of antibiotic for aquaculture use among six types of commonly-used antibiotics (ampicillin, kanamycin, tetracycline, nalidixic acid, furazolidone and sulphamethoxazole). In the present study, antibiotic susceptibility test against local E. tarda was tested using disk diffusion and two-fold microdilution method was applied to determine its sensitivity and Minimum Inhibitory Concentration (MIC) values, respectively. The results showed that antibiotic sensitivity and resistance cases were reported as 63.0 % and 28.7 %, respectively. Intermediary sensitivity case was recorded as 8.3 %. The MIC value of the 6 antibiotics against the present isolates ranged from 1 mg/L to equal or more than 128 mg/l. 12 out of 18 isolates were found to carry plasmid where the sizes of plasmids were in the range of 54kb to 300 bp. All the isolates from cultured freshwater fish were found to carry plasmid except for Isolate T2. Only 4 (E1, G1, G2 and G3) out of 9 isolates from wild freshwater fish were found to carry plasmid, whereas Isolate E2, E3, E3, E4, G4 and G5 did not possess any plasmid. The total number of plasmid carried by the present isolates ranged from 1 to 8 plasmids. No correlation was found between the incidence of antibiotic resistance and plasmid carried by the present isolates. MAR index revealed that cultured freshwater fish in Terengganu received high-risk exposure to the tested antibiotics. On the other hand, wild freshwater fish were under the level of exposure to the antibiotics. Overall, ampicillin, kanamycin, tetracycline, nalidixic acid and furazolidone were successfully found to inhibit more than 50 % of the present bacterial isolates. On the other hand, more than 80 % of bacterial isolates were resistant to sulphamethoxazole. In terms of MIC values, ampicillin and nalidixic acid showed the lowest MIC value (1 mg/l) to control the growth of E. tarda. Therefore, we suggested that ampicillin and nalidixic acid can be used for combating Edwardsiellosis due to E. tarda in freshwater